2010
DOI: 10.1097/pec.0b013e3181fb0e23
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Disability in Children With Unexplained Chest Pain Presenting to the Pediatric Emergency Department

Abstract: Objective: Chest pain is a common presentation in the pediatric emergency department (PED). In the majority of cases, no clear medical cause is found. Among adults with noncardiac chest pain, psychopathology including panic disorder is common. We assessed the likelihood and type of psychopathology as well as the health status of children and adolescents with unexplained chest pain who presented to the PED.Methods: We performed a semistructured diagnostic interview of children 8 to 17 years old who presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
3
14
2
1
Order By: Relevance
“…In two preliminary studies we identified high rates of psychiatric disorders in youth with unexplained chest pain (12,13). We undertook a case-control study comparing youth seen in outpatient cardiology consultation for medically unexplained chest pain to a control sample of youth with innocent heart murmur.…”
mentioning
confidence: 99%
“…In two preliminary studies we identified high rates of psychiatric disorders in youth with unexplained chest pain (12,13). We undertook a case-control study comparing youth seen in outpatient cardiology consultation for medically unexplained chest pain to a control sample of youth with innocent heart murmur.…”
mentioning
confidence: 99%
“…These findings also demonstrate that while some pediatric NCCP patients do meet criteria for panic disorder or another anxiety disorder, a number do not; this emphasizes that at least some NCCP patients suffer from a singular ailment that is distinct from undiagnosed panic or anxiety disorder. Still, the relatively small and homogenous samples utilized in these studies limits the generalizability of these findings and indicates the need for replication with larger, more diverse samples [13,15].…”
Section: Psychopathologymentioning
confidence: 86%
“…Unfortunately, details regarding the nature of the psychiatric interviews used in these three studies [27][28][29] are not reported. Structured diagnostic interviews demonstrated lower prevalence of depression, with 8-19% of patients meeting DSM-IV diagnostic criteria for a depressive disorder [13,15], although again the small sample sizes constitute a limitation. However, standardized self-report measures also suggest a lower rate of depression, with 11% of patients reporting elevated depressive symptoms, comparable to depressive symptoms reported by patients with benign heart murmurs [14].…”
Section: Psychopathologymentioning
confidence: 98%
See 2 more Smart Citations